Health and safety in construction guidance for construction professionals - Barber, John, FCIArb (Thomas Telford, 2002)
This title offers clear guidance on the responsibilities of construction professionals for health and safety in construction. Construction professionals need to work together to ensure consistently high standards and this essential guide will help achieve a measured and effective response to this challenge.